The punishment as ritual of initiation in Indigenous Justice: Women mothers, social fighters and intellectual training Ayuujk (Oaxaca, México) - Roque Urbieta Hernández (Les Cahiers ALHIM)
Single mothers, social fighters and protagonists of the indigenous student movement in the struggle for community education in the Normal Experimental School of Cempoaltepelt have organized themselves in the lost decade in Latin America. The experience of the Ayuujk women spans different political actions as organic intellectual. It is crucial for the formation of indigenous autonomy in Santa María Tlahutoltepec, Mixe (Oaxaca, Mexico). Therefore, the professionalization of the leadership of indigenous women in the international arena needs rethinking in a diachronic perspective. The significance that “punishment” has for them, as a “ritual of initiation” in the attempt to access spaces of community participation in the system of charges, leading to becoming the subject of human rights, allows us to rethink the meaning acquired by female leaders in indigenous communities in four historical blocs: crisis of institutional indigenism, penetration of the State, struggle for community education and experiences of political actors as leaders. In short, before 1995, the Ayuujk women’s movement within the Oaxaca indigenous movement has revealed the reconfiguration of the nation-state and its shift to the neoliberal Pluricultural State.